Village Community Participation in Supporting SDGs in Lugusari Village, Pringsewu Regency - Haros, Saskia Susanti; Tabrani, Syifa; Meitasuci, Dzulfiana; Lailiah, Hidayatul; Andari, Renanda; Wulandari, Fitri (Program Studi Perencanaan Wilayah dan Kota, UPT Publikasi Publikasi Ilmiah UNISBA, 2024)
The Ministry of Villages, Development of Disadvantaged Regions and Transmigration issued Ministerial Regulation Number 21 of 2020 as general guidelines for village stakeholders in carrying out development and empowerment of village communities in harmony with the Village SDGs. In achieving village development planning, community participation is needed, in order to achieve common goals. The aim of this research is to find out how the community participates in village SDGs in the development of Lugusari Village, Pringsewu Regency. This research was conducted in September 2023, using the census method with a total of 45 respondents consisting of village officials and village communities. The method used in this research is descriptive quantitative by collecting data through interviews, observation and documentation. The results of this research show that community participation is classified as quite good in terms of community knowledge regarding village SDGs, as well as participation in planning and reporting village SDGs to build local wisdom and village potential to achieve the welfare of the Lugusari Village community. Based on the survey results, it shows that when reporting on Village SDGs, the community plays an active role in reporting and participating in programs provided by the government, both the village government and the regional government of Pringsewu Regency.